2010
DOI: 10.1097/olq.0b013e3181c9963a
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Male Circumcision for the Prevention of HIV Among High-Risk Heterosexual Men in Thailand

Abstract: Limited data are available on circumcision prevalence and acceptability among Thai men to prevent human immunodeficiency virus. Of 408 high-risk heterosexual men, 12.3% were circumcised. 14.2% and 24.9% expressed willingness to be circumcised before and after circumcision education, respectively. Neonatal circumcision acceptability was relatively high. One participant underwent circumcision at 3-month follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 7 publications
2
20
0
Order By: Relevance
“…However, on the basis of the RCTs and the Cochrane review, researchers are now raising the possibility of incorporating male circumcision into HIV prevention initiatives in regions such as Papua New Guinea (Hill et al, 2012;Kelly et al, 2012), the Dominican Republic (Brito, Caso, Balbuena, & Bailey, 2009), the Caribbean (Duncan, 2010) and Thailand (Tieu et al, 2010). Although the rise of EBM enabled the 'male circumcision effect' to be taken as given, can we assume that the operation would have the same effect globally?…”
Section: Debating the Evidencementioning
confidence: 98%
“…However, on the basis of the RCTs and the Cochrane review, researchers are now raising the possibility of incorporating male circumcision into HIV prevention initiatives in regions such as Papua New Guinea (Hill et al, 2012;Kelly et al, 2012), the Dominican Republic (Brito, Caso, Balbuena, & Bailey, 2009), the Caribbean (Duncan, 2010) and Thailand (Tieu et al, 2010). Although the rise of EBM enabled the 'male circumcision effect' to be taken as given, can we assume that the operation would have the same effect globally?…”
Section: Debating the Evidencementioning
confidence: 98%
“…While the prevalence of MC worldwide is almost 30%, only 5% of Chinese males are circumcised [12]. While the acceptability of MC has been studied in men and women in sub-Saharan Africa [13], [14], the United States [15], and Thailand [16], no population-level studies, with large sample size, prior to ours have been conducted in China, especially targeting general population. An earlier study assessed MC acceptability among MSM [17], which reported very low level of MC acceptability (16.9% would absolutely willing to participate and 26.4% would probably participate).…”
Section: Introductionmentioning
confidence: 99%
“…182,183 Although a recent study in India suggests that circumcised MSM who predominantly take the receptive role in anal intercourse may be at a lower risk of HIV infection, 184 evidence that circumcision reduces HIV among MSM remains weak and inconsistent. 185,186 Despite the willingness to undergo circumcision among MSM populations, 187,188 male circumcision is not promoted as a priority in Asian countries with concentrated epidemics and has not been recommended for MSM unless they also engage in vaginal sex. 148 It is therefore unlikely that male circumcision will significantly contribute to reducing the HIV incidence among MSM populations.…”
Section: Implications For Hiv Prevention Trialsmentioning
confidence: 99%